KEPUASAN MAHASISWA TERHADAP KONDISI PEMBELAJARAN PADA MATA KULIAH KOMPREHENSIF SETELAH MASA PANDEMI COVID-19 - Marchita, Livia; Afrimonika, Yoanna; Suhardi, Suhardi (Universitas Tanjungpura, 2023)
The Covid-19 virus has made major changes in human life, especially in the field of Education. As a country that attaches importance to the quality of education, of course, Indonesia continues to strive to improve the effectiveness of learning. In this effort, students as a result of learning is one of the important keys. Therefore, researchers want to compare the student satisfaction of offline and online learning in Chinese comprehensive courses which are divided into 4 aspects (teachers and learning, students, learning environment, and use of resources and facilities). The object of this research is a student majoring in Chinese Language Education, Tanjungpura University, Class of 2020. Therefore, researchers use questionnaires as an instrument in collecting data. This study used a 5-point Likert scale in analyzing and collecting satisfaction scores from students and using descriptive methods in explaining the data that had been processed. The results showed that the level of satisfaction in offline learning was higher than online learning